China na ONU: Operações de Paz, Segurança e Desenvolvimento - Alexandre, Leonardo Soares (2023)
The rise of China in recent decades is a phenomenon that has generated debates and studies regarding its potential impact on several areas of the international order. Among them, it is possible to highlight the areas of development and security. Related to these two areas, there are references in the literature about the existence of a distinctly Chinese approach to peace, which contains strategies for conflict resolution involving development and security, also known as developmental peace. This work seeks to analyze China's behavior in these sectors from the perspective of the UN and Peacekeeping Operations, of which China is a key player, with the aim of verifying whether the country promotes its development and security agenda through its participation in these operations. To that end, a case study was conducted focusing on China's engagement in the resolution of the conflict in South Sudan, the country that receives the highest number of Chinese peacekeepers, in order to ascertain if China's behavior contains elements of developmental peace. The evidence gathered by the study seems to confirm the application of these elements in the context of the South Sudanese conflict, positioning China's development and security agenda as a possible alternative to the liberal agenda in UN Peacekeeping Operations